Bioelectrical impedance vector analysis and phase angle to verify early hydration status and prognosis in hospitalized children with nephrotic syndrome: an exploratory case series - da Silva, Esther Artuanne Figueredo; de Araújo, Mayara Gabrielly Germano; Xavier, Ana Márcia Soares Fernandes; Dantas, Ana Karina da Costa; da Silva, Eduardo Paixão; Lopes, Márcia Marília Gomes Dantas (Frontiers in Nutrition, 2025)
BackgroundChildren with nephrotic syndrome (NS) represent a high-risk group for significant clinical and nutritional alterations. The scarcity of studies on rapid and practical methods for assessing hydration status and nutritional prognosis in this context highlights the need for this study.AimTo investigate the body composition profile through bioelectrical impedance vector analysis (BIVA) and to evaluate the phase angle (PhA) between groups of hospitalized children with nephrotic syndrome (NS).MethodsIn this study, we present nine cases of hospitalized children diagnosed with NS. The cases were divided into two groups: symptomatic NS (G1) and asymptomatic NS (G2). Upon hospital admission, socioeconomic, clinical, and biochemical data were collected, along with nutritional screening, anthropometric assessment (height-for-age), and body composition analysis using BIVA and PhA calculation.ResultsMost children were male (67%) with a median age of 42 months. Most of the cases received social benefits, and their mothers had completed high school. All patients presented some degree of risk of malnutrition, regardless of symptomatology. BIVA identified anasarca and low body cell mass in the G1 group, whereas the G2 group showed a tendency toward leanness and cachexia. The PhA was significantly lower in group G1 (median = 2.49°, IQR = 1.04) compared to G2 (median = 3.68°, IQR = 0.60) (p = 0.036).ConclusionBIVA rapidly and early detected extracellular water accumulation and reduced body cell mass, highlighting that those individuals with symptomatic NS had a lower PhA, suggesting a less favorable prognosis.